STRATEGI PENYULUH AGAMA DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN PADA ANAK DI TPA AL-MUKHLISIN KABUPATEN PANGKEP - Rusdi, Muhammad; Syahruddin, Asri (Istiqra: jurnal hasil penelitian, 2022)
This research discusses the strategies of religious instructors in improving the ability to read the Qur'an in children at TPA AL-Mukhlisin, Tumampua Village, Pangkajene District, Pangkep Regency. The methodology used in this research is qualitative, the data collection techniques used are observation, interviews and documentation. Research findings show that the strategies used by ustadz to teach the Koran to children at AL-Mukhlisin TPA include the iqro method, wafa method, and habituation method. Meanwhile, regarding obstacles, there is a lack of time allocated for the program and low motivation for some students. The solutions offered are improving the quality of teachers and counselors, extending time allocation, and improving learning facilities